Efektivitas Model Pembelajaran Collaborative Problem Solving Ditinjau dari Kemampuan Penalaran Matematis Siswa SMP - Vira Hidayatunnisa; Rini Asnawati; Mella Triana (Jurnal Pendidikan Matematika : Judika Education, 2025)
This research aims to test the effectiveness of the collaborative problem solving learning model in terms of students' mathematical reasoning skills. The method used is pretest-posttest control group design. This study involved students in grades VII-C and VII-F of SMP Negeri 1 Natar in the 2024/2025 academic year. The findings obtained were that (1) The mathematical reasoning skills of students who follow the collaborative problem solving model increases higher than the mathematical reasoning skills of students who follow the direct learning model; (2) The proportion of students who participate in collaborative problem solving learning who have mathematical reasoning skills categorized as good is more than 60%.; and (3) the average posttest score of students exceeded the KKM. The conclusion from the findings above is that the collaborative problem solving learning model is effective in terms of mathematical reasoning skills and can be a reference for teachers or other researchers.   Keywords: Collaborative problem solving, Effective, Mathematical reasoning     skills